Shore girl, sure thing : discursive construction and maintenance of a sexual stereotype : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Manawatū, New Zealand - Gatland, Susanna Mary (Massey University, 2014)
Young women from Auckland’s North Shore are the subjects of negative, gender-based stereotyping, as articulated in the catch-phrase “Shore girl, sure thing”. Within the North Shore itself, negative stereotypes also exist for women from particular schools or suburbs. The current forms of these stereotypes appear to have only been prevalent since the 1990s, and are very different to those about young women from the area in previous years. These stereotypes are produced through dominant sexual discourses that function to maintain and reproduce a sexual double standard for women, and to reinforce existing patriarchal power structures. However, these stereotypes also draw on multiple intersecting discourses. This research examines the “Shore Girl” stereotype to enable the opening of spaces for resistance and for challenging these normative and oppressive discourses. Analysis of conversational interviews with twelve women representing two age groups was conducted to interrogate the dominant discourses involved in the construction, maintenance and change of the stereotype over time and how they produce positions for women. A feminist poststructuralist epistemology was utilised to enable exploration of the patriarchal power structures involved in the discourses, how this power regulates women’s subjectivity and the social function of the “Shore Girl” stereotype in maintaining patriarchal dominance and the social status quo. It also enabled examination of the resistance exercised by the women towards the “Shore Girl” stereotype. Analysis included examination of the way in which the women located themselves and others in relation to space and place, and the co-construction of person and place. The construction of place-based identities established the relational landscape within which the stereotypes’ meaning was produced. Two key findings were that women’s privilege is represented as sexualised in other places through dominant discourses and that whiteness is constructed as normative as part of an ongoing process of colonisation. Future research could question and challenge the processes of subjectification within normative discourses of sexuality that sexualise women’s privilege and also normalisation of whiteness as part of a process of decolonisation.
Keywords: Young women, New Zealand; Sexism, Auckland; Sexism, North Shore, New Zealand; Social perceptions; Gender stereotypes; Patriarchy